International Diplomacy for International Management - Bogatinskaia, Liudmila; Bahles, Michael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how project managers employ diplomatic strategies to facilitate and enhance international collaborations at the intersection of clinical research and information technology. The central research question explores the approaches used by project managers to foster successful partnerships within the healthcare sector, specifically in clinical trials. The study adopts a mixed-methods approach, incorporating both a comprehensive literature review and qualitative interviews with project managers. The literature review critically examines existing diplomatic strategies in international healthcare collaborations and analyzes regulatory frameworks governing clinical research. The empirical component includes interviews with experienced project managers, offering qualitative insights into the practical application of diplomacy in cross-cultural project management. Drawing on diplomatic management theory, this research emphasizes the role of diplomatic principles in managing complex, global healthcare projects. Additionally, the study integrates organizational diplomacy and negotiation theories to assess how effective diplomatic communication can improve collaboration in clinical trials. By employing this theoretical framework, the thesis seeks to highlight best practices and methods for navigating the unique challenges of international healthcare project management.
Vedoucí práce: Michael Bahles
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses